2021
DOI: 10.20546/ijcrbp.2021.805.003
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of genetic diversity among different Rose (Rosa) genotypes using morphological and molecular markers (ISSR)

Abstract: Rose is a woody perennial of the genus Rosa within the family Rosaceae. In this study, phylogenetic relationship among seven different genotypes of Rose (Rosa) was determined using ISSR primers and morphological parameters. DNA was isolated using CTAB method with 0.5% of CTAB concentration. Out of 50 ISSR primers, 16 primers gave reproducible banding pattern with all the seven genotypes of Rose while others failed to produce polymorphism. A total of 108 bands were obtained with an average polymorphism of 54.69… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…Morphological and genetic study of the Kakinada rose revealed that it clusters with R. damascena var. Himroz, a local variation from South India [16]. A great degree of variation was found in the rose germplasm according to both morphological and molecular analyses, making it a priceless source of genetic diversity for improving roses.…”
Section: Resultsmentioning
confidence: 99%
“…Morphological and genetic study of the Kakinada rose revealed that it clusters with R. damascena var. Himroz, a local variation from South India [16]. A great degree of variation was found in the rose germplasm according to both morphological and molecular analyses, making it a priceless source of genetic diversity for improving roses.…”
Section: Resultsmentioning
confidence: 99%